(untitled) (Journal of Social Sciences Review, 2023)
In light of the evolving corporate landscape and the growing emphasis on competencies and strategic approaches, the concept of Green Human Resource Management (HRM) has emerged as a vital component of global green development. Green HRM integrates environmental considerations into HR activities, contributing to the long-term sustainability of organizations and their workforce. While existing literature has predominantly focused on sustainability, this research addresses the novel contribution of Green HRM. The study examines the impact of Green HRM practices on the sustainability of Pakistan’s manufacturing industry, encompassing social, environmental, and economic performance indicators. Data were collected from 111 manufacturing employees in Pakistan, utilizing a convenience sampling method and structured questionnaires. The findings reveal that Green HRM positively influences the environmental, economic, and social performance management practices of emerging economies. Companies with a strong brand image can leverage Green HRM practices to enhance sales and consumer awareness, aligning with their green objectives. Consequently, manufacturing enterprises in Pakistan can enhance their clean industrial capacity by adopting the proposed investigation model.